Hydrogen injection reduces ammonia nitrogen and changes microbial community composition in aquaculture water - Ning, Shengdi; Hu, Junru; Yu, Jie; Huang, Long; Lai, Minjian; Li, Xiangni; Lin, Yongchun; Zhong, Wanqing; Wang, Lei (Frontiers in Marine Science, 2023)
The study aimed to investigate the effect of hydrogen on nitrogen and phosphorus removal and microbial community composition in aquaculture water. Two groups were designed separated: Group H was charged with hydrogen and Group D was set as control. Water samples were collected at 0, 1, 2, 3, 4, 5, 6, and 7 days after hydrogen injection to detect not only the content of total nitrogen, ammonia nitrogen and phosphorus, but also microbial community composition in aquaculture water. Our findings have demonstrated that 7-days’ hydrogen treatment could effectively reduce ammonia nitrogen in aquaculture water. And in Day 7, the concentration of ammonia nitrogen in Group D was 1.66 times as that in Group H. Meanwhile, microbial structures in the water bodies of these two groups were significantly different. The abundance of bacteria such as Proteobacteria, Firmicutes, Bacteroidetes, and Desulphuria increased clearly in Group H, which means nitrification and denitrification occurred in the effect of hydrogen injection. These findings suggested that hydrogen could significantly improve aquaculture water health and reduce the production of ammonia nitrogen, which means hydrogen could be used as a functional external method to protect the aquaculture environment.